The lung clearance index as a monitoring tool in cystic fibrosis: ready for the clinic?. Issue 6 (November 2018) - Perrem, Lucy; Rayment, Jonathan H.; Ratjen, Felix
Abstract : Purpose of review: In cystic fibrosis, (CF) there is an urgent need for objective tests that can capture and track preclinical lung disease. The lung clearance index (LCI), the primary outcome measure of the multiple breath washout test, is an established endpoint in clinical trials but the clinical utility of the test remains poorly defined. The purpose of this review is to examine the key studies over the past years that have advanced our understanding of the role of the LCI in clinical practice. Recent findings: The variability of LCI measurements increases with lung disease severity, and new evidence shows that between-visit changes in the LCI are therefore best expressed as a relative rather than an absolute change. A relative change of greater than 15% between visits is likely outside the intrinsic variability of the test and physiologically relevant. The LCI is feasible to perform and is a more sensitive outcome measure than forced expiratory volume in one second (FEV1). The LCI correlates with outcome measures such as structural MRI, and shows great promise in the routine clinical monitoring of CF lung disease, particularly in younger patients with milder disease. Summary: Recent studies have progressed our understanding of the role of the LCI in clinical practice, but the exact clinical utility of the test in monitoring CF lung disease is still uncertain.